Crisis of global sustainability - Kanninen, Tapio (New York : Routledge, 2013)
"The book provides a critical history of the concept of sustainability and the various institutional measures taken to promote, implement and enforce sustainable development"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Club of Rome; Sustainable development -- Government policy; Sustainable development; Electronic books